Positive–negative-selection-mediated gene targeting in rice - Shimatani, Zenpei; Nishizawa-Yokoi, Ayako; Endo, Masaki; Toki, Seiichi; Terada, Rie (Frontiers in Plant Science, 2015)
Gene targeting (GT) refers to the designed modification of genomic sequence(s) through homologous recombination (HR). GT is a powerful tool both for the study of gene function and for molecular breeding. However, in transformation of higher plants, non-homologous end joining (NHEJ) occurs overwhelmingly in somatic cells, masking HR-mediated GT. Positive-negative selection (PNS) is an approach for finding HR-mediated GT events because it can eliminate NHEJ effectively by expression of a negative-selection marker gene. In rice—a major crop worldwide—reproducible PNS-mediated GT of endogenous genes has now been successfully achieved. The procedure is based on strong PNS using diphtheria toxin A-fragment as a negative marker, and has succeeded in the directed modification of several endogenous rice genes in various ways. In addition to gene knock-outs and knock-ins, a nucleotide substitution in a target gene was also achieved recently. This review presents a summary of the development of the rice PNS system, highlighting its advantages. Different types of gene modification and gene editing aimed at developing new plant breeding technology (NPBT) based on PNS are discussed.